Analisis Prolematika Perkembangan Bahasa pada Anak Kelas III Madrasah Ibtidaiyah Negeri Lima Puluh Kota - Asril, Muthia; Putri, Nadila; Adrias, Adrias; Suciana, Fadila (Fakultas Sastra Universitas Muslim Indonesia, 2025)
This study aims to describe the problems of language development among third-grade students at Madrasah Ibtidaiyah Negeri Lima Puluh Kota. The research focuses on identifying the factors that influence children’s language abilities, including family environment, school context, and psychological aspects. This research employed a qualitative descriptive method. Data were collected through observation, interviews, and documentation involving teachers and students. The data were analyzed through thematic reduction, display, and conclusion drawing. The findings reveal that children’s language difficulties are influenced by limited verbal stimulation at home, low social interaction at school, and the lack of varied learning media. Conversely, teacher support and a communicative learning environment help students overcome these difficulties. This study highlights the importance of collaboration between teachers and parents in creating a literacy-friendly environment that fosters language development among elementary school children.